2018
DOI: 10.5014/ajot.2018.027870
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapist–Delivered Cognitive–Behavioral Therapy for Knee Osteoarthritis: A Randomized Pilot Study

Abstract: An online-supported cognitive-behavioral program for people with KOA delivered by occupational therapists is feasible and may contribute to improved physical function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…There were two primary aims to teaching general relaxation, rstly to initiate the process of postural deconstruction (see below) and secondly to raise consciousness of both emotional and muscular responses to pain. This focus is consistent with previous research supporting the use of relaxation interventions for arthritis pain [90] and the use of cognitive behavioural therapy interventions which incorporate relaxation for knee OA [20]. We speci cally targeted three easy-to-observe characteristics of relaxation.…”
Section: Component 2: General Relaxationmentioning
confidence: 69%
See 1 more Smart Citation
“…There were two primary aims to teaching general relaxation, rstly to initiate the process of postural deconstruction (see below) and secondly to raise consciousness of both emotional and muscular responses to pain. This focus is consistent with previous research supporting the use of relaxation interventions for arthritis pain [90] and the use of cognitive behavioural therapy interventions which incorporate relaxation for knee OA [20]. We speci cally targeted three easy-to-observe characteristics of relaxation.…”
Section: Component 2: General Relaxationmentioning
confidence: 69%
“…During this period, there have been continual re nements in the frequency, duration and nature of the exercises [11] along with the addition of self-management components which aim to provide reassurance about the value of exercise in OA [17]. While there has been some focus on adjunctive therapies [18], such as cognitive-behavioural therapy [19,20], there has been very little research investigating biopsychosocial interventions for knee OA [21], despite suggestions that this may improve clinical management [22,23]. This is particularly concerning given the evidence of strong links between psychosocial factors and clinical pain/disability in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reason for the greater variance in ATQ-N, KDS, STAI-KYZ, and COPM shown by the experimental group is likely to be due to the effect of the CBT. Murphy et al [ 37 ] conducted a study on patients with osteoarthritis and found a notable beneficial effect of the CBT on pain and fatigue, thus providing a focused discussion on the high level of treatment satisfaction in the participants. In line with this, both the experimental and control groups in this study showed a significant improvement in the two items of COPM, while the variance was increased to a greater degree in the experimental group than in the control group with a particularly large improvement in the satisfaction, which may be attributed to the beneficial effect of CBT including the change towards positive thoughts and feelings and enhanced self-esteem and self-confidence, combined with the previously described positive effect of the occupation-based bilateral upper limb training.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational therapy research in the United States has established credible evidence that effective interventions conducted in traditional service contexts (i.e., outpatient) have a positive impact on sequelae of chronic medical conditions, including low vision (Barstow et al, 2015) and arthritis (Murphy et al, 2018), and on medication adherence for patients with those conditions (Schwartz et al, 2017). In addition, international research has demonstrated that population health benefits can be achieved through occupational therapy's integration into models of primary care and can provide a platform to conduct ongoing research in the United States (Mackenzie et al, 2013;Richardson et al, 2010).…”
Section: Feasible Solutions To Integrate Occupational Therapymentioning
confidence: 99%